﻿Balitora anlongensis, the first cavefish species of the genus Balitora (Teleostei, Balitoridae) from Guizhou Province, southwest China - Tao Luo; Zhi-Xia Chen; Xin-Rui Zhao; Jing Yu; Chang-Ting Lan; Jia-Jun Zhou; Ning Xiao; Jiang Zhou (ZooKeys, 2023)
This work describes a new species, Balitora anlongensis sp. nov., collected from a cave at Xinglong Town, Anlong County, Guzihou, China. Phylogenetic trees reconstructed based on two mitochondrial and three nuclear genes show that the new species represents an independent evolutionary lineage with large genetic differences, 7.1%–12.0% in mitochondrial gene cytochrome b and 9.2%–12.1% in cytochrome oxidase subunit 1, from congeners. Morphologically, the new species can be distinguished from the 18 species currently assigned to the genus Balitora by a combination of characters, most clearly by having two pairs of maxillary barbels; 8½ branched dorsal-fin rays; 5½ branched anal-fin rays; pectoral fin not reaching pelvic fin origin; dorsal-fin origin in front of pelvic fin origin; eye small (eye diameter approximately equal to outer maxillary barbel length); and fins lacking pigment in live fish. The new species represents the first record of Balitora inhabiting caves in China and increases the number of species in the genus Balitora in its present concept from 18 to 19. The study suggests that more evidence is needed to further clarify the taxonomic composition of the genus Balitora.